CURABLE RESIN COMPOSITION, DRY FILM AND CURED PRODUCT THEREOF, AND ELECTRONIC COMPONENTS COMPRISING THE CURED PRODUCT

JP7630940B2Active Publication Date: 2025-02-18TAIYO HOLDINGS CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2020147328
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-06
Filing Date
2020-09-02
Publication Date
2025-02-18
Estimated Expiration
2040-09-02

Smart Images

  • Figure 0007630940000001
    Figure 0007630940000001
  • Figure 0007630940000002
    Figure 0007630940000002
  • Figure 0007630940000003
    Figure 0007630940000003
Patent Text Reader

Abstract

To provide a curable resin composition improved in developability and resolution without deteriorating heat resistance and chemical resistance, a dry film containing the same, a cured product thereof, and a printed wiring board including the cured product.SOLUTION: The curable resin composition is obtained which contains (A) an amide-imide resin, (B) a compound having an ethylenic double bond, and (C) a photopolymerization initiator. The amide-imide resin (A) is a reaction product of a tricarboxylic acid anhydride and an isocyanurate type polyisocyanate synthesized from an isocyanate having an aliphatic structure and has a number average molecular weight of 500-1,000.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a curable resin composition, for example, a curable resin composition for an interlayer insulating material used in rewiring or the like of a printed wiring board, particularly a curable resin composition, a dry film and a cured product of the curable resin composition, and an electronic part containing the cured product. [Background technology]

[0002] Conventionally, a curable resin composition containing an amide-imide resin has been used as an interlayer insulating material for a printed wiring board to improve various properties such as heat resistance of the cured product. In particular, when the amide-imide resin contains a carboxyl group, it is possible to alkali develop a coating film of the curable resin composition. However, even when an amide-imide resin containing a carboxyl group is used, the developability or resolution is not necessarily good (for example, Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2003-221429 A DISCLOSURE OF THEINVENTION [Problem to be solved by the invention]

[0004] Therefore, in a curable resin composition containing an amide-imide resin, when a large amount of a carboxyl group-containing resin is further contained in addition to the amide-imide resin in order to improve resolution, the glass transition temperature (Tg) tends to decrease, and the chemical resistance of the obtained cured product may decrease. In particular, when the cured product is used in a form that includes a part of the substrate of an electronic component, the substrate surface is washed with an acid or alkali during the preparation of the substrate, and washed with a solvent during mounting, so that the chemical resistance of the substrate is essential. However, to date, a resin composition that is excellent in all properties, such as heat resistance, developability, resolution, and chemical resistance, has not been obtained.

[0005] Therefore, an object of the present invention is to provide a curable resin composition having improved developability and resolution without reducing heat resistance and chemical resistance, a dry film containing the same, a cured product thereof, and a printed wiring board containing the cured product. [Means for solving the problem]

[0006] In view of the above object, the present inventors have conducted extensive research and have found that (A) an amide-imide resin; (B) a compound having an ethylenic double bond; (C) a photopolymerization initiator; The present inventors have found a curable resin composition comprising the above-mentioned formula (A), wherein the amide-imide resin (A) is a reaction product between an isocyanurate-type polyisocyanate synthesized from an isocyanate having an aliphatic structure and a tricarboxylic acid anhydride, and has a number average molecular weight of 500 to 1000, and have completed the present invention.

[0007] The tricarboxylic acid anhydride of the present invention preferably has an aliphatic structure.

[0008] The curable resin composition of the present invention preferably further contains (D) a thermosetting resin.

[0009] The above-mentioned object of the present invention is achieved by a dry film including a resin layer constituted from the above-mentioned curable resin composition, a cured product of the curable resin composition, and an electronic component including the cured product. Effect of the Invention

[0010] According to the present invention, it is possible to obtain a curable resin composition having excellent heat resistance and chemical resistance after curing and improved developability and resolution, a dry film thereof, a cured product thereof, and a printed wiring board including the cured product. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] The curable resin composition of the present invention contains (A) an amide-imide resin, (B) a compound having an ethylenic double bond, and (C) a photopolymerization initiator, and the (A) amide-imide resin is a reaction product of an isocyanurate-type polyisocyanate synthesized from an isocyanate having an aliphatic structure and a tricarboxylic acid anhydride, and has a number average molecular weight of 500 to 1,000. The curable resin composition of the present invention has the above-mentioned constitution, and when it is subjected to development with an alkaline developer, it exhibits excellent developability, and the resolution of the cured product obtained is very good. In addition, the cured product obtained from this curable resin composition is also excellent in heat resistance, cured coating strength, and chemical resistance. Therefore, it is useful in applications that require both fine resolution and coating durability (heat resistance, strength, chemical resistance), such as interlayer insulating materials for printed wiring boards and insulating materials for rewiring.

[0012] Each of the components of the curable resin composition will be described in detail below.

[0013] [(A) Amide-imide resin] The curable resin composition of the present invention contains (A) an amide-imide resin. The (A) amide-imide resin is produced by reacting an isocyanurate-type polyisocyanate synthesized from an isocyanate having an aliphatic structure with a tricarboxylic anhydride, and one having a number-average molecular weight in the range of 500 to 1000 is used. That is, the (A) amide-imide resin used in the present invention is produced by directly forming an imide bond from the above-mentioned isocyanurate-type polyisocyanate and a tricarboxylic anhydride, and an amide-imide resin having good material stability, reproducibility, and solubility and excellent transparency can be synthesized compared to the synthesis via a polyamic acid intermediate in the conventional technology. In addition, by setting the number-average molecular weight of the (A) amide-imide resin in the range of 500 to 1000, the developability and resolution are particularly improved.

[0014] [Isocyanurate-type polyisocyanate] (A) The above-mentioned isocyanurate type polyisocyanate, which is used as a raw material for synthesizing the amide-imide resin, is synthesized from an aliphatic isocyanurate, i.e., an aliphatic linear isocyanate (e.g., hexamethylene diisocyanate, trimethylhexamethylene diisocyanate) or an alicyclic isocyanate (isophorone diisocyanate, hydrogenated tolylene diisocyanate, hydrogenated xylene diisocyanate, norbornane diisocyanate, hydrogenated diphenylmethane diisocyanate).

[0015] Specific examples of isocyanurate polyisocyanates include: HDI3N: Isocyanurate-type triisocyanate synthesized from hexamethylene diisocyanate, HTMDI3N: Isocyanurate type triisocyanate synthesized from trimethylhexamethylene diisocyanate. IPDI3N: Isocyanurate triisocyanate synthesized from isophorone diisocyanate. HTDI3N: Isocyanurate type triisocyanate synthesized from hydrogenated tolylene diisocyanate. HXDI3N: Isocyanurate triisocyanate synthesized from hydrogenated xylene diisocyanate. NBDI3N: an isocyanurate-type triisocyanate synthesized from norbornane diisocyanate, and HMDI3N: An isocyanurate-type triisocyanate synthesized from hydrogenated diphenylmethane diisocyanate. The above triisocyanurates may be used alone or in combination.

[0016] The isocyanate used as the raw material of the (A) amide-imide resin is preferably an alicyclic isocyanate, particularly isophorone diisocyanate, and the use of this improves Tg and provides a cured coating film with excellent thermal properties. In addition, since the isocyanate having the aliphatic structure does not have an aromatic ring structure, the amide-imide resin according to the present invention obtained thereby has high transparency.

[0017] [Tricarboxylic acid anhydride] (A) Examples of tricarboxylic anhydrides, which are other reaction raw materials for the amide-imide resin, include tricarboxylic anhydrides having an aromatic structure, such as trimellitic anhydride and 1,2,4-benzenetricarboxylic 1,2 anhydride, and tricarboxylic anhydrides having an aliphatic structure (including an aliphatic linear structure or an alicyclic structure), such as cyclohexanetricarboxylic anhydride, methylcyclohexanetricarboxylic anhydride, cyclohexenetricarboxylic anhydride, and methylcyclohexenetricarboxylic anhydride. As the tricarboxylic anhydride, those having an aliphatic structure are preferred, and cyclohexanetricarboxylic anhydride is particularly preferred. The isocyanurate-type polyisocyanate and the tricarboxylic anhydride are preferably those having no aromatic ring structure. As a result, the amide-imide resin according to the present invention obtained has high transparency, and the cured product obtained from the curable resin composition of the present invention containing it also has high transparency.

[0018] Cyclohexanetricarboxylic anhydride is represented by the following formula (1):

[0019] [ka] Specific examples thereof include cyclohexane-1,3,4-tricarboxylic acid-3,4-anhydride, cyclohexane-1,3,5-tricarboxylic acid-3,5-anhydride, and cyclohexane-1,2,3-tricarboxylic acid-2,3-anhydride. In particular, cyclohexane-1,3,4-tricarboxylic acid-3,4-anhydride is preferably used. That is, by using such an aliphatic tricarboxylic acid anhydride as the raw material for the amide-imide resin (A), the heat resistance of the cured product of the present invention is made even more excellent.

[0020] In addition, as a raw material for producing the (A) amide-imide resin, the above-mentioned tricarboxylic acid anhydride may be used in combination with a bifunctional dicarboxylic acid compound, for example, an aliphatic or aromatic dicarboxylic acid, such as sebacic acid, phthalic acid, fumaric acid, maleic acid, and acid anhydrides thereof, in some cases.

[0021] When the carboxylic acid component of the tricarboxylic anhydride reacts with the isocyanate component in the isocyanurate polyisocyanate, imide and amide are formed, and the resin of the present invention becomes an amide-imide resin. When the isocyanurate polyisocyanate reacts with the tricarboxylic anhydride, an imide bond is formed from the acid anhydride group and the isocyanate group, and an amide bond is formed from the carboxyl group and the isocyanate group. However, when the tricarboxylic anhydride group and the polyisocyanate group are reacted in such a ratio that the carboxylic acid (carboxyl group) component of the tricarboxylic anhydride remains, the resulting polyamide-imide resin has a carboxyl group. This carboxyl group reacts with a polymerizable group such as an epoxy group of the epoxy resin contained in the curable resin composition of the present invention described later, and forms a crosslinked structure of the cured product. In addition, in the reaction between the tricarboxylic anhydride and the triisocyanate, the above-mentioned two types of reactions, amidation and imidation, are considered, but the reaction rate of imidization is fast, so the tricarboxylic acid selectively forms an imide at the acid anhydride group.

[0022] It is preferable to react an isocyanurate type polyisocyanate synthesized from an isocyanate having an aliphatic structure with a tricarboxylic anhydride having an aliphatic structure so that the ratio of the number of moles (N) of the isocyanate group of the isocyanurate type polyisocyanate synthesized from the isocyanate having an aliphatic structure to the total number of moles (M1) of the carboxyl group of the tricarboxylic anhydride and the number of moles (M2) of the acid anhydride group [(M1) + (M2)) / (N)] is 1.1 to 3, because the polarity in the reaction system is high and the reaction proceeds smoothly, no isocyanate group remains, the stability of the obtained polyimide resin is good, the amount of remaining tricarboxylic anhydride is small, and separation problems such as recrystallization are unlikely to occur. Among them, 1.2 to 2 is more preferable. In the present invention, the acid anhydride group refers to a -CO-O-CO- group obtained by intramolecular dehydration condensation of two carboxylic acid molecules.

[0023] The imidization reaction is preferably carried out by mixing one or more isocyanates having an aliphatic structure with one or more tricarboxylic acid anhydrides in a solvent or without a solvent, and raising the temperature while stirring. The reaction temperature is preferably 50°C to 250°C, and particularly preferably 70°C to 180°C. By setting the reaction temperature at such a temperature, the reaction rate is increased and side reactions and decomposition are less likely to occur. In the reaction, the acid anhydride group and the isocyanate group form an imide group while decarbonating. The progress of the reaction can be tracked by analytical means such as infrared spectroscopy, acid value, and quantitative determination of isocyanate groups. In infrared spectroscopy, the characteristic absorption of the isocyanate group at 2270 cm -1 decreases with the reaction and further increases to 1860cm -1 and 850cm -1 The acid anhydride group, which has a characteristic absorption at 1780cm, is decreased. -1 and 1720cm -1The absorption of the imide group increases as the reaction proceeds. The reaction may be terminated by lowering the temperature while checking the target acid value, viscosity, molecular weight, etc. However, it is more preferable to continue the reaction until the isocyanate group disappears in terms of stability over time, etc. In addition, during or after the reaction, a catalyst, an antioxidant, a surfactant, other solvents, etc. may be added within a range that does not impair the physical properties of the resin to be synthesized.

[0024] The acid value of the amide-imide resin of the present invention is preferably 70 to 210 KOHmg / g, and particularly preferably 90 to 190 KOHmg / g. If it is 70 to 210 KOHmg / g, excellent performance is exhibited as cured physical properties. The amide-imide resin of the present invention is preferably an amide-imide resin that dissolves in a polar solvent that does not contain either a nitrogen atom or a sulfur atom. An example of such an amide-imide resin is a branched amide-imide resin having a branched structure and an acid value of 60 KOHmg / g or more.

[0025] The (A) amide-imide resin in the curable resin composition has a number average molecular weight Mn of 500-1,000, and preferably 700-900. In the present invention, when the (A) amide-imide resin has a number-average molecular weight Mn of 500 or more, the heat resistance of the cured coating film becomes good. When the number-average molecular weight Mn is 1,000, contrast is easily achieved when the curable resin composition is developed, and the obtained cured coating film has excellent resolution. In the present invention, unless otherwise specified, the number average molecular weight is determined by gel permeation chromatography (GPC) using polystyrene as a standard. The content of the (A) amide-imide resin is preferably in the range of 30 to 85 mass %, particularly 40 to 70 mass %, based on the total mass of the solid content of the curable resin composition, because the blending amount in this range improves the Tg of the curable resin composition and provides a cured coating film with excellent thermal properties.

[0026] [(B) Compound having an ethylenic double bond] The curable resin composition of the present invention contains (B) a compound having an ethylenic double bond. (B) The compound having an ethylenic double bond is photocured by irradiation with active energy rays, and can make or help make the resin composition of the present invention insoluble in an alkaline aqueous solution.

[0027] Specific examples of the compound (B) having an ethylenic double bond include: Monoacrylates having a hydroxyl group, such as hydroxyalkyl acrylates such as 2-hydroxyethyl acrylate and 2-hydroxypropyl acrylate; Diacrylates of glycols such as ethylene glycol, methoxytetraethylene glycol, polyethylene glycol, and propylene glycol; Acrylamides such as N,N-dimethylacrylamide, N-methylol acrylamide, and N,N-dimethylaminopropyl acrylamide; Aminoalkyl acrylates such as N,N-dimethylaminoethyl acrylate and N,N-dimethylaminopropyl acrylate; Alkyl diols such as hexanediol, nonanediol, and decanediol; polyhydric alcohols such as trimethylolpropane, pentaerythritol, dipentaerythritol, isocyanurate, and tris-hydroxyethyl isocyanurate; or polyhydric acrylates such as their ethylene oxide adducts, propylene oxide adducts, and ε-caprolactone adducts; bifunctional acrylates such as 1,6-hexanediol diacrylate, 1,9-nonanediol diacrylate, and 1,10-decanediol diacrylate; trimethylolpropane triacrylate, pentaerythritol triacrylate, and tris(2-hydroxyethyl) Trifunctional acrylates such as isocyanurate triacrylate, ethylene oxide modified trimethylol triacrylate, ethylene oxide modified trimethylolpropane triacrylate, propylene oxide modified trimethylolpropane triacrylate, ε-caprolactone modified tris-(2-acryloxyethyl)isocyanurate, tetrafunctional acrylates such as ditrimethylolpropane tetraacrylate, pentaerythritol tetraacrylate, ethoxylated pentaerythritol tetraacrylate, pentafunctional acrylates such as dipentaerythritol pentaacrylate, hexafunctional acrylates such as dipentaerythritol hexaacrylate, phenoxy acrylate, bisphenol A diacrylate, and esters of these phenols. Examples of the acrylates include polyhydric acrylates such as ethylene oxide adducts or propylene oxide adducts; polyhydric acrylates of glycidyl ethers such as glycerin diglycidyl ether, glycerin triglycidyl ether, trimethylolpropane triglycidyl ether, and triglycidyl isocyanurate; acrylates having a dicyclopentadiene skeleton such as dicyclopentadiene diacrylate; and, without being limited to the above, acrylates and melamine acrylates obtained by directly acrilating polyols such as polyether polyols, polycarbonate diols, hydroxyl-terminated polybutadienes, and polyester polyols or by urethane acrylate via diisocyanates, as well as methacrylates corresponding to the above acrylates.

[0028] Further examples include epoxy (meth)acrylate resins obtained by reacting (meth)acrylic acid with a multifunctional epoxy resin such as a cresol novolac epoxy resin, and epoxy urethane acrylate compounds obtained by reacting a half urethane compound of a hydroxy acrylate such as pentaerythritol triacrylate and a diisocyanate such as isophorone diisocyanate with the hydroxyl group of the epoxy acrylate resin. Such epoxy acrylate resins can improve photocurability without reducing dryness to the touch. The (B) compound having an ethylenically unsaturated group may be used alone or in combination of two or more kinds. The (B) compound having an ethylenically unsaturated group is added in a ratio of preferably 0.1 to 25 parts by mass, more preferably 3 to 20 parts by mass, relative to 100 parts by mass of the solid content of the curable resin composition. By setting the blending amount of the (B) compound having an ethylenically unsaturated group to 0.1 parts by mass or more relative to 100 parts by mass of the solid content of the curable resin composition, the photocurability of the curable resin composition becomes good, and by setting it to 20 parts by mass or less, halation due to an excessive photopolymerization reaction can be prevented and good resolution can be obtained.

[0029] [(C) Photopolymerization initiator] The curable resin composition of the present invention includes a photopolymerization initiator (C). As the photopolymerization initiator (C), any known and commonly used material can be used without any particular limitation. In particular, as described below, an oxime ester type having a structure represented by general formula (I), an α-aminoacetophenone type having a structure represented by general formula (II), an acylphosphine oxide type having a structure represented by general formula (III), and a titanocene type having a structure represented by general formula (IV) can be used. The (C) photopolymerization initiator may be used alone or in combination of two or more kinds.

[0030] [Oxime ester photoinitiators]

[0031] [ka] The oxime ester photoinitiator is represented by the above general formula (I), and in general formula (I), R1 represents a hydrogen atom, a phenyl group, an alkyl group, a cycloalkyl group, an alkanoyl group, or a benzoyl group. R2 represents a phenyl group, an alkyl group, a cycloalkyl group, an alkanoyl group, or a benzoyl group. The phenyl group represented by R1 and R2 may have a substituent, and examples of the substituent include an alkyl group having 1 to 6 carbon atoms, a phenyl group, and a halogen atom. The alkyl group represented by R1 and R2 is preferably an alkyl group having 1 to 20 carbon atoms, and may contain one or more oxygen atoms in the alkyl chain. It may also be substituted with one or more hydroxyl groups. The cycloalkyl group represented by R1 and R2 is preferably a cycloalkyl group having 5 to 8 carbon atoms. The alkanoyl group represented by R1 and R2 is preferably an alkanoyl group having 2 to 20 carbon atoms. The benzoyl group represented by R1 and R2 may have a substituent, and examples of the substituent include an alkyl group having 1 to 6 carbon atoms, a phenyl group, and the like.

[0032] Specific examples of the oxime ester photopolymerization initiator of general formula (I) include 1,2-octanedione-1-[4-(phenylthio)-2-(O-benzoyloxime)], ethanone, 1-[9-ethyl-6-(2-methylbenzoyl)-9H-carbazol-3-yl]-, 1-(O-acetyloxime), etc. Commercially available products include CGI-325, Irgacure OXE01, Irgacure OXE02 manufactured by BASF Japan, N-1919, NCI-831, etc. manufactured by Adeka Corporation. Photopolymerization initiators having two oxime ester groups in the molecule and photopolymerization initiators having a carbazole structure can also be used suitably.

[0033] [α-Aminoacetophenone photoinitiator]

[0034] [ka] The α-aminoacetophenone photoinitiator is represented by the above general formula (II), in which R3 and R4 each independently represent an alkyl group or an arylalkyl group having 1 to 12 carbon atoms, and R5 and R6 each independently represent a hydrogen atom or an alkyl group having 1 to 6 carbon atoms, or two of them may be bonded to form a cyclic alkyl ether group.

[0035] Specific examples of α-aminoacetophenone-based photopolymerization initiators that can be used include commercially available compounds such as (4-morpholinobenzoyl)-1-benzyl-1-dimethylaminopropane (Omnirad 369, product name, manufactured by IGM Resins), 4-(methylthiobenzoyl)-1-methyl-1-morpholinoethane (Omnirad 907, product name, manufactured by IGM Resins), and 2-(dimethylamino)-2-[(4-methylphenyl)methyl]-1-[4-(4-morpholinyl)phenyl]-1-butanone (Omnirad 379, product name, manufactured by IGM Resins), or solutions thereof.

[0036] [Acylphosphine oxide photoinitiators]

[0037] [ka] The acylphosphine oxide photoinitiator is represented by the above general formula (III), in which R7 and R8 each independently represent an alkyl group having 1 to 10 carbon atoms, a cycloalkyl group having 5 to 8 carbon atoms such as a cyclopentyl group or a cyclohexyl group, an aryl group, or an aryl group substituted with a halogen atom, an alkyl group, or an alkoxy group, or a carbonyl group having 1 to 20 carbon atoms (excluding the case where both are carbonyl groups having 1 to 20 carbon atoms).

[0038] Specific examples of the acylphosphine oxide photopolymerization initiator include 2,4,6-trimethylbenzoyldiphenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-phenylphosphine oxide, bis(2,6-dimethoxybenzoyl)-2,4,4-trimethyl-pentylphosphine oxide, etc. Commercially available products include Omnirad TPO manufactured by IGM Resins, Omnirad 819 manufactured by IGM Resins, etc.

[0039] [Titanocene photoinitiators]

[0040] [ka] The titanocene photoinitiator is represented by the above general formula (IV), in which R9 and R10 each independently represent a halogen atom, an aryl group, a halogenated aryl group, or a heterocycle-containing halogenated aryl group.

[0041] Titanocene photopolymerization initiators include bis(η5-2,4-cyclopentadiene-1-yl)-bis(2,6-difluoro-3-(1H-pyrrol-1-yl)-phenyl)titanium. Commercially available products include Irgacure 784 manufactured by BASF Japan Ltd. In this specification, halogen or halogen atom means fluorine, chlorine, bromine or iodine, and aryl means monocyclic aromatic hydrocarbon groups such as phenyl groups and polycyclic aromatic hydrocarbon groups such as naphthyl groups.

[0042] Other photopolymerization initiators that can be used in the present invention include, for example, benzoin and benzoin alkyl ethers such as benzoin, benzoin methyl ether, benzoin ethyl ether, and benzoin isopropyl ether; anthraquinones such as 2-methylanthraquinone, 2-ethylanthraquinone, 2-t-butylanthraquinone, 1-chloroanthraquinone, and 2-amylanthraquinone; thioxanthones such as 2,4-dimethylthioxanthone, 2,4-diethylthioxanthone, 2-chlorothioxanthone, and 2,4-diisopropylthioxanthone; ketals such as acetophenone dimethyl ketal and benzyl dimethyl ketal; benzophenones such as benzophenone; xanthones; various peroxides such as 3,3',4,4'-tetra-(tert-butylperoxycarbonyl)benzophenone; and 1,7-bis(9-acridinyl)heptane.

[0043] In the curable resin composition of the present invention, in addition to the above photopolymerization initiator, one or more of known and commonly used photosensitizers such as tertiary amines such as N,N-dimethylaminobenzoic acid ethyl ester, N,N-dimethylaminobenzoic acid isoamyl ester, pentyl-4-dimethylaminobenzoate, triethylamine, triethanolamine, etc. may be used in combination. Furthermore, when a deeper photocuring depth is required, a 3-substituted coumarin dye, leuco dye, etc. may be used in combination as a curing assistant, as necessary.

[0044] The (C) photopolymerization initiator is generally added in a ratio of 0.1 to 50 parts by mass, more preferably 1 to 30 parts by mass, per 100 parts by mass of the solid content of the curable resin composition. If the blending amount of the (C) photopolymerization initiator is within the above range per 100 parts by mass of the solid content of the curable resin composition, the photocuring reaction is favorably promoted.

[0045] [(D) Thermosetting resin] The curable resin composition of the present invention may further contain (D) a thermosetting resin. Examples of (D) thermosetting resin include known thermosetting resins such as polyfunctional epoxy compounds, polyfunctional oxetane compounds, episulfide resins, etc., compounds having two or more cyclic ether groups and / or cyclic thioether groups in a molecule, polyisocyanate compounds, blocked isocyanate compounds, etc., compounds having two or more isocyanate groups or blocked isocyanate groups in one molecule, melamine resins, benzoguanamine resins, etc., amine resins and derivatives thereof, bismaleimide, oxazine, cyclocarbonate compounds, carbodiimide resins, etc.

[0046] As the polyfunctional epoxy resin, a known and commonly used polyfunctional epoxy resin having at least two epoxy groups in one molecule can be used. The epoxy resin may be liquid, solid or semi-solid. Examples of polyfunctional epoxy resins include, but are not limited to, bisphenol A type epoxy resins, brominated epoxy resins, novolac type epoxy resins, bisphenol F type epoxy resins, hydrogenated bisphenol A type epoxy resins, glycidylamine type epoxy resins, hydantoin type epoxy resins, alicyclic epoxy resins, trihydroxyphenylmethane type epoxy resins, bixylenol type or biphenol type epoxy resins or mixtures thereof, bisphenol S type epoxy resins, bisphenol A novolac type epoxy resins, tetraphenylolethane type epoxy resins, heterocyclic epoxy resins, diglycidyl phthalate resins, tetraglycidylxylenoylethane resins, naphthalene group-containing epoxy resins, epoxy resins having a dicyclopentadiene skeleton, glycidyl methacrylate copolymer epoxy resins, cyclohexylmaleimide and glycidyl methacrylate copolymer epoxy resins, epoxy-modified polybutadiene rubber derivatives, and CTBN-modified epoxy resins. The epoxy resin is preferably a bisphenol A or bisphenol F novolac type epoxy resin, a bixylenol type epoxy resin, a biphenol type epoxy resin, a biphenol novolac type (biphenyl aralkyl type) epoxy resin, a naphthalene type epoxy resin, or a mixture thereof.

[0047] From the viewpoint of improving heat resistance, epoxy resins having an aromatic ring skeleton (for example, a naphthalene skeleton) are preferred, and from the viewpoint of improving resolution, epoxy resins having an alicyclic skeleton are preferred.

[0048] Examples of epoxy resins having an aromatic ring skeleton include epoxy resins having a naphthalene skeleton, particularly aralkyl-type naphthalene. In this epoxy resin having a naphthalene skeleton, naphthalene has a planar structure, and it is possible to reduce the linear expansion coefficient and further improve heat resistance. Examples of commercially available epoxy resins having a naphthalene skeleton include ESN-190 and ESN-360 manufactured by Nippon Steel Chemical Industry Co., Ltd., EPICRON HP-4032, EPICRON, and HP-4032D manufactured by DIC Corporation, and NC-7000L manufactured by Nippon Kayaku Co., Ltd. Furthermore, examples of epoxy resins having an alicyclic skeleton include epoxy resins having a dicyclopentadiene skeleton. The epoxy resins having an alicyclic skeleton are expected to have a higher glass transition temperature than epoxy resins having a chain skeleton.

[0049] The thermosetting resins as described above may be used alone or in combination of two or more kinds. When the (D) thermosetting resin is used, the blending amount is 5 to 20 parts by mass per 100 parts by mass of the solid content of the curable resin composition, whereby both the developability of the curable resin composition and the heat resistance and resolution of the cured product are extremely excellent.

[0050] [(E) Carboxyl group-containing resin] In order to further improve the developability, the curable resin composition of the present invention may optionally contain (E) a carboxyl group-containing resin. The (E) carboxyl group-containing resin is a compound having a structure different from the above-mentioned (A) amide-imide resin, and may be a photosensitive or non-photosensitive resin having a carboxyl group in the molecule without containing an amide-imide structure. Specific examples thereof include the following (E1) to (E10).

[0051] Specific examples of the non-photosensitive carboxyl group-containing resin include the following compounds (which may be either oligomers or polymers). (E1) A carboxyl group-containing resin obtained by copolymerizing an unsaturated carboxylic acid such as (meth)acrylic acid with an unsaturated group-containing compound such as styrene, α-methylstyrene, lower alkyl (meth)acrylate, or isobutylene.

[0052] (E2) Carboxyl group-containing urethane resins obtained by polyaddition reaction of diisocyanates such as aliphatic diisocyanates, branched aliphatic diisocyanates, alicyclic diisocyanates, and aromatic diisocyanates with carboxyl group-containing dialcohol compounds such as dimethylolpropionic acid and dimethylolbutanoic acid, and diol compounds such as compounds having phenolic hydroxyl groups and alcoholic hydroxyl groups including polycarbonate polyols, polyether polyols, polyester polyols, polyolefin polyols, acrylic polyols, and bisphenol A alkylene oxide adduct diols.

[0053] (E3) A terminal carboxyl group-containing urethane resin obtained by reacting an acid anhydride with the terminal of a urethane resin obtained by polyaddition reaction of a diisocyanate compound such as an aliphatic diisocyanate, a branched aliphatic diisocyanate, an alicyclic diisocyanate, or an aromatic diisocyanate with a diol compound such as a polycarbonate-based polyol, a polyether-based polyol, a polyester-based polyol, a polyolefin-based polyol, an acrylic polyol, or a compound having a phenolic hydroxyl group and an alcoholic hydroxyl group, including a bisphenol A-based alkylene oxide adduct diol.

[0054] (E4) Carboxyl group-containing photosensitive urethane resins obtained by polyaddition reaction of diisocyanates with (meth)acrylates of bifunctional epoxy resins such as bisphenol A type epoxy resins, hydrogenated bisphenol A type epoxy resins, bisphenol F type epoxy resins, bisphenol S type epoxy resins, bixylenol type epoxy resins, and biphenol type epoxy resins, or their partial acid anhydride modified products, carboxyl group-containing dialcohol compounds, and diol compounds.

[0055] (E5) A photosensitive urethane resin containing a carboxyl group, which is terminated with (meth)acrylation by adding a compound having one hydroxyl group and one or more (meth)acryloyl groups in the molecule, such as a hydroxyalkyl (meth)acrylate, during the synthesis of the resin (E2) or (E4) described above.

[0056] (E6) A carboxyl group-containing photosensitive urethane resin having a terminal (meth)acrylation obtained by adding a compound having one isocyanate group and one or more (meth)acryloyl groups in the molecule, such as an equimolar reactant of isophorone diisocyanate and pentaerythritol triacrylate, during the synthesis of the above-mentioned resin (E2) or (E4).

[0057] (E7) A carboxyl group-containing photosensitive resin obtained by reacting a bifunctional or more polyfunctional epoxy resin as described below with (meth)acrylic acid and adding a dibasic acid anhydride such as phthalic anhydride, tetrahydrophthalic anhydride, or hexahydrophthalic anhydride to the hydroxyl groups present in the side chains. Here, the epoxy resin is preferably solid.

[0058] (E8) A carboxyl group-containing photosensitive resin obtained by reacting a polyfunctional epoxy resin, in which the hydroxyl groups of a bifunctional epoxy resin as described below are further epoxidized with epichlorohydrin, with (meth)acrylic acid, and then adding a dibasic acid anhydride to the resulting hydroxyl groups. Here, the epoxy resin is preferably in a solid state.

[0059] (E9) A carboxyl group-containing photosensitive resin obtained by adding a cyclic ether such as ethylene oxide or a cyclic carbonate such as propylene carbonate to a polyfunctional phenol compound such as novolac, partially esterifying the resulting hydroxyl groups with (meth)acrylic acid, and reacting the remaining hydroxyl groups with a polybasic acid anhydride.

[0060] (E10) A carboxyl group-containing photosensitive resin obtained by further adding a compound having one epoxy group and one or more (meth)acryloyl groups in the molecule, such as glycidyl (meth)acrylate, α-methylglycidyl (meth)acrylate, to any of the resins (E1) to (E9).

[0061] (E11) A carboxyl group-containing photosensitive resin obtained by reacting a compound having a plurality of phenolic hydroxyl groups in one molecule, i.e., a polyphenol compound (e.g., phenol novolac, cresol novolac), with an alkylene oxide such as ethylene oxide or propylene oxide to obtain a reaction product such as a polyalcohol resin, with an unsaturated group-containing monocarboxylic acid such as (meth)acrylic acid, and further reacting the obtained reaction product with a polybasic acid anhydride.

[0062] (E12) A carboxyl group-containing photosensitive resin obtained by reacting a polyphenol compound (e.g., phenol novolac, cresol novolac) with a cyclic carbonate compound such as ethylene carbonate or propylene carbonate, reacting the reaction product obtained with an unsaturated group-containing monocarboxylic acid, and reacting the resulting reaction product with a polybasic acid anhydride. In the present invention, photosensitive carboxyl group-containing photosensitive resins having a polyphenol skeleton, such as the above (E11) and (E12), are preferably used.

[0063] The (E) carboxyl group-containing resin may be used alone or in combination of two or more kinds. However, the total mass is preferably 1 part by mass or more and 40 parts by mass or less per 100 parts by mass of the solid content of the (A) amide-imide resin, which improves the developability of the curable resin composition and the resolution of the cured product.

[0064] [Inorganic filler] The curable resin composition of the present invention may further contain an inorganic filler that is used in ordinary resin compositions. Specific examples of such fillers include non-metallic fillers such as silica, barium sulfate, calcium carbonate, silicon nitride, aluminum nitride, boron nitride, alumina, magnesium oxide, aluminum hydroxide, magnesium hydroxide, titanium oxide, mica, talc, Neuburg silica, and organic bentonite, and metal fillers such as copper, gold, silver, palladium, and silicon. In the curable resin composition of the present invention, these inorganic fillers may be used alone or in combination of two or more. In the present invention, it is preferable to use barium sulfate, silica, or both of them.

[0065] The content of these inorganic fillers is 5 to 60 mass % relative to the total mass of the solid content of the curable resin composition of the present invention, and is particularly preferably 10 to 50 mass %. By appropriately selecting the blending amount depending on the type of inorganic filler, it is possible to improve the strength of the cured coating film without decreasing the resolution.

[0066] [Other ingredients] The curable resin composition of the present invention may contain other components in addition to the above components, provided that the effects of the present invention are not impaired. Examples of additives that may be blended include silicone-based and fluorine-based defoamers, leveling agents, heat curing accelerators, heat polymerization inhibitors, ultraviolet absorbers, solvents, silane coupling agents, plasticizers, foaming agents, flame retardants, antistatic agents, antioxidants, antibacterial and antifungal agents, etc.

[0067] In addition, a solvent can be used to adjust the viscosity of the curable resin composition to an appropriate level for application to a substrate or a carrier film. As such a solvent, mainly organic solvents are used, and specific examples thereof include ketones, aromatic hydrocarbons, glycol ethers, glycol ether acetates, esters, alcohols, aliphatic hydrocarbons, and petroleum-based solvents. More specifically, the organic solvents include ketones such as methyl ethyl ketone and cyclohexanone; aromatic hydrocarbons such as toluene, xylene, and tetramethylbenzene; glycol ethers such as cellosolve, methyl cellosolve, butyl cellosolve, carbitol, methyl carbitol, butyl carbitol, propylene glycol monomethyl ether, dipropylene glycol monomethyl ether, dipropylene glycol diethyl ether, and triethylene glycol monoethyl ether; esters such as ethyl acetate, butyl acetate, dipropylene glycol methyl ether acetate, propylene glycol methyl ether acetate, propylene glycol ethyl ether acetate, and propylene glycol butyl ether acetate; alcohols such as ethanol, propanol, ethylene glycol, and propylene glycol; aliphatic hydrocarbons such as octane and decane; and petroleum-based solvents such as petroleum ether, petroleum naphtha, hydrogenated petroleum naphtha, and solvent naphtha. One of these organic solvents may be used alone, or two or more of them may be used in combination.

[0068] The curable resin composition of the present invention may be a liquid type, or may be a dry film type obtained by drying a liquid type resin composition. The liquid type resin composition may be a two-liquid type or the like from the viewpoint of storage stability, but may also be a one-liquid type. Hereinafter, a dry film will be described in detail as one embodiment of the curable resin composition.

[0069] [Dry film manufacturing] The dry film of the present invention has a resin layer obtained by applying the curable resin composition of the present invention onto a film (hereinafter also referred to as a "carrier film") and then drying. The dry film of the present invention can be obtained by diluting the curable resin composition of the present invention with an organic solvent to adjust the viscosity to an appropriate level, applying the composition to a uniform thickness onto a carrier film using a comma coater, blade coater, lip coater, rod coater, squeeze coater, reverse coater, transfer roll coater, gravure coater, spray coater, or the like, and generally drying the composition at a temperature of 50 to 130°C for 1 to 30 minutes. There is no particular restriction on the coating thickness, but the coating thickness after drying may be appropriately set in the range of generally 3 to 100 μm, preferably 5 to 40 μm.

[0070] As the carrier film, a plastic film can be suitably used, and it is preferable to use a plastic film such as a polyester film such as polyethylene terephthalate, a polyimide film, a polyamideimide film, a polypropylene film, a polystyrene film, etc. There is no particular limitation on the thickness of the carrier film, but it is generally appropriately selected in the range of 10 to 150 μm.

[0071] After the curable resin composition of the present invention is applied onto the carrier film and dried, a peelable film (hereinafter also referred to as a "cover film") may be laminated on the surface of the coating film for the purpose of preventing dust from adhering to the surface of the coating film, etc. Examples of the peelable cover film that can be used include polyethylene film, polytetrafluoroethylene film, polypropylene film, surface-treated paper, etc., and any film may be used as long as the adhesive strength between the coating film and the cover film is smaller than the adhesive strength between the coating film and the carrier film when the cover film is peeled off.

[0072] The drying treatment carried out after the curable resin composition of the present invention is applied onto a carrier film is carried out using a hot air circulation drying oven, an IR oven, a hot plate, a convection oven or the like, thereby obtaining a dry film.

[0073] When the curable resin composition is applied directly onto a substrate, examples of the substrate include printed wiring boards and flexible printed wiring boards on which circuits have been preformed, as well as all grades (e.g., FR-4) of copper-clad laminates for high-frequency circuits made of materials such as paper phenol, paper epoxy, glass cloth epoxy, glass polyimide, glass cloth / non-woven epoxy, glass cloth / paper epoxy, synthetic fiber epoxy, fluorine-polyethylene-polyphenylene ether, polyphenylene oxide-cyanate ester, and the like, as well as polyimide films, PET films, glass substrates, ceramic substrates, wafer plates, and the like.

[0074] [Production of cured product] A cured product (cured film) using the curable resin composition of the present invention is produced as follows. That is, first, the curable resin composition is diluted with a solvent as necessary, and then coated on a substrate. The pattern formation of the curable resin composition is performed by selectively exposing (irradiating light) the resin layer obtained after evaporating and drying the solvent, and curing the exposed parts (parts irradiated with light). Thereafter, the unexposed parts are developed with an alkaline aqueous solution (for example, a 0.3 to 3 mass % aqueous solution of sodium carbonate), thereby forming a pattern of the coating film. Furthermore, the curable resin composition is irradiated with light to perform a photocured coating film, and a cured coating film is formed.

[0075] The coating method may be any of the following: dip coating, flow coating, bar coating, and screen printing. As the light source for irradiating the active energy rays, a low pressure mercury lamp, a medium pressure mercury lamp, a high pressure mercury lamp, an ultra-high pressure mercury lamp, a xenon lamp, or a metal halide lamp is suitable. In addition, UV-LED, laser beams, electron beams, and the like can also be used as the active energy rays.

[0076] The volatilization drying carried out after coating can be carried out using a hot air circulation drying oven, an IR oven, a hot plate, a convection oven, etc. (a method in which hot air in the dryer is brought into countercurrent contact with the substrate using a heat source that uses steam for air heating, or a method in which hot air is blown onto the substrate from a nozzle).

[0077] The dried curable resin composition or dry film can be exposed to active energy rays by contact or non-contact through a photomask having a pattern formed thereon. In addition, the exposed portion can be photocured by directly exposing the curable resin composition or dry film to a pattern using a laser direct exposure machine.

[0078] Here, the exposure machine used for irradiating the active energy rays may be a device equipped with a high pressure mercury lamp, an ultra-high pressure mercury lamp, a metal halide lamp, a mercury short arc lamp, or the like, and capable of irradiating ultraviolet rays in the range of 350 to 450 nm. Furthermore, a direct imaging device such as a direct imaging device that directly draws an image with active energy rays based on CAD data from a computer may also be used. The light source of the direct imaging device may be a mercury short arc lamp, an LED, or any of a gas laser and solid laser as long as it uses laser light with a maximum wavelength in the range of 350 to 410 nm. The exposure dose for forming an image on the patterned resin layer varies depending on the film thickness, etc., but is generally 20 to 1,500 mJ / cm. 2 , preferably 20 to 1,200 mJ / cm 2 The range may be:

[0079] As the developing method, a dipping method, a shower method, a spray method, a brush method, or the like can be adopted, and as the developing solution, an alkaline aqueous solution of potassium hydroxide, sodium hydroxide, sodium carbonate, potassium carbonate, sodium phosphate, sodium silicate, ammonia, amines, or the like can be used.

[0080] Furthermore, the curable resin composition of the present invention can be irradiated with active energy rays at a concentration of, for example, 50 mJ / cm 2 ~1500mJ / cm 2The composition can be photocured by irradiating the composition with a light source within the range of 100 to 180° C. The photoirradiation is carried out by irradiating the composition with active energy rays such as ultraviolet rays, electron beams, and chemical rays, preferably ultraviolet rays. When the curable resin composition contains a thermosetting component, the composition can be heated to a temperature of about 100 to 180° C. after photocuring to perform thermal curing (post-cure), thereby promoting the curing of the coating film.

[0081] The curable resin composition of the present invention is applicable to electronic parts. In the present invention, the term "parts used in electronic circuits" refers to active parts such as printed wiring boards, light-emitting diodes, and laser diodes, as well as passive parts such as resistors, capacitors, inductors, and connectors, and the cured coating film of the curable composition of the present invention exhibits the effects of the present invention. The curable resin composition of the present invention is particularly suitable for forming an insulating cured coating for printed wiring boards, and is further suitable for forming permanent insulating films such as coverlays, solder resists, interlayer insulating materials, and insulating materials for forming rewiring layers.

[0082] An electronic component including a cured product obtained from the curable resin composition of the present invention can fully exhibit its functions as an electronic component because the cured product has excellent resolution and heat resistance. In addition, the cured product obtained from the curable resin composition of the present invention has excellent chemical resistance, so that it does not deteriorate or deform due to the chemicals used, even when cleaning with acids or alkalis during the production of a substrate or cleaning with a solvent during mounting, and the precision of the electronic component can be maintained or improved. EXAMPLES

[0083] The following are examples. Reference example, The present invention will be described in more detail with reference to the following comparative examples. The present invention is not limited to the following examples, and all "parts" and "%" described below are based on mass unless otherwise specified.

[0084] [Synthesis of raw materials] [Production of amide-imide resin] Synthesis Example 1: (A) Synthesis of Amide-imide Resin 1 5184g of EDGA (diethylene glycol monoethyl ether acetate), 2070g (3mol) of IPDI3N (isocyanurate type triisocyanate synthesized from isocyanurate: NCO%=18.2) and 1782g (9mol) of cyclohexane-1,3,4-tricarboxylic acid-3,4-anhydride were added to a flask equipped with a stirrer, a thermometer and a condenser, and the temperature was raised to 140°C. The reaction proceeded with foaming. The reaction was allowed to proceed at this temperature for 8 hours. The liquid in the system became pale yellow, and the characteristic absorption of the isocyanate group at 2270cm-1 was completely disappeared by infrared spectroscopy, and the absorption of the imide group was confirmed at 1780cm-1 and 1720cm-1. The acid value was 140KOHmg / g in terms of solid content, and the molecular weight was 800 in terms of number average molecular weight in terms of polystyrene. The concentration of the resin content was 40% by weight. This resin solution is referred to as (A) amide-imide resin 1 solution.

[0085] Synthesis Example 2: (A') Synthesis of Amide-imide Resin 2 4628g of EDGA (diethylene glycol monoethyl ether acetate), 2070g (3mol) of IPDI3N (isocyanurate type triisocyanate synthesized from isocyanurate: NCO%=18.2) and 1386g (7mol) of cyclohexane-1,3,4-tricarboxylic acid-3,4-anhydride were added to a flask equipped with a stirrer, a thermometer and a condenser, and the temperature was raised to 140°C. The reaction proceeded with foaming. The reaction was allowed to proceed at this temperature for 8 hours. The liquid in the system became pale yellow, and the characteristic absorption of the isocyanate group at 2270cm-1 was completely disappeared by infrared spectroscopy, and the absorption of the imide group was confirmed at 1780cm-1 and 1720cm-1. The acid value was 140KOHmg / g in terms of solid content, and the molecular weight was 5800 in terms of number average molecular weight in terms of polystyrene. The concentration of the resin content was 40% by weight. This resin solution is referred to as (A') amide-imide resin 2 solution.

[0086] Synthesis Example 3: (A') Synthesis of Amide-imide Resin 3 4903g ​​of EDGA (diethylene glycol monoethyl ether acetate), 2070g (3mol) of IPDI3N (isocyanurate type triisocyanate synthesized from isocyanurate: NCO%=18.2) and 1683g (8.5mol) of cyclohexane-1,3,4-tricarboxylic acid-3,4-anhydride were added to a flask equipped with a stirrer, a thermometer and a condenser, and the temperature was raised to 140°C. The reaction proceeded with foaming. The reaction was allowed to proceed at this temperature for 8 hours. The liquid in the system became pale yellow, and the characteristic absorption of the isocyanate group at 2270cm-1 was completely disappeared by infrared spectroscopy, and the absorption of the imide group was confirmed at 1780cm-1 and 1720cm-1. The acid value was 140KOHmg / g in terms of solid content, and the molecular weight was 1500 in terms of number average molecular weight in terms of polystyrene. The concentration of the resin content was 40% by weight. This resin solution is referred to as (A′) amide-imide resin 3 solution.

[0087] Synthesis Example 4 (A) Synthesis of Amide-imide Resin 4 3554g of EDGA (diethylene glycol monoethyl ether acetate), 2070g (3mol) of IPDI3N (isocyanurate type triisocyanate synthesized from isocyanurate diisocyanate: NCO%=18.2) and 1333g (9mol) of 1,2,4-benzenetricarboxylic acid 1,2-anhydride were added to a flask equipped with a stirrer, a thermometer and a condenser, and the temperature was raised to 140°C. The reaction proceeded with foaming. The reaction was allowed to proceed at this temperature for 8 hours. The system turned into a brown liquid, and the characteristic absorption of the isocyanate group at 2270cm-1 was completely disappeared by infrared spectroscopy, and the absorption of the imide group was confirmed at 1780cm-1 and 1720cm-1. The acid value was 140KOHmg / g in terms of solid content, and the molecular weight was 800 in terms of number average molecular weight in terms of polystyrene. The concentration of the resin content was 40% by weight. This resin solution is referred to as an amide-imide resin 4 solution.

[0088] The number average molecular weights of the amide-imide resins 1 to 4 were measured by gel permeation chromatography (GPC) (polystyrene standard) using the following measuring device and under the following measuring conditions.

[0089] Device name: Waters 2695 Detector: Waters 2414 refractive index (RI) detector Column: Waters, high-speed analytical HSPgel column, HR MB-L, 3μm, 6mm×150mm×2, and Waters, HSPgel column, HR1, 3μm, 6mm×150mm×2 Measurement conditions: Column temperature: 40℃ RI detector temperature setting: 35℃ Developing solvent: Tetrahydrofuran Flow rate: 0.5ml / min Sample volume: 10μl Sample concentration: 0.5wt%

[0090] Synthesis Example 5: Synthesis of carboxyl group-containing resin In an autoclave equipped with a thermometer, a nitrogen introduction device / alkylene oxide introduction device, and a stirrer, 119.4g of novolac cresol resin (manufactured by Showa Polymer Co., Ltd., product name "Shounol CRG951", OH equivalent: 119.4), 1.19g of potassium hydroxide, and 119.4g of toluene were charged, and the system was replaced with nitrogen while stirring, and the temperature was raised by heating. Next, 63.8g of propylene oxide was gradually dropped, and the reaction was carried out for 16 hours at 125-132℃ and 0-4.8kg / cm2. After that, the reaction solution was cooled to room temperature, and 1.56g of 89% phosphoric acid was added and mixed to neutralize the potassium hydroxide, and a propylene oxide reaction solution of novolac cresol resin with a nonvolatile content of 62.1% and a hydroxyl value of 182.2g / eq. was obtained. This product had an average of 1.08 moles of alkylene oxide added per equivalent of phenolic hydroxyl group. 293.0 g of the resulting alkylene oxide reaction solution of the novolac cresol resin, 43.2 g of acrylic acid, 11.53 g of methanesulfonic acid, 0.18 g of methylhydroquinone, and 252.9 g of toluene were charged into a reactor equipped with a stirrer, a thermometer, and an air inlet tube, and reacted at 110°C for 12 hours while blowing air at a rate of 10 ml / min and stirring. 12.6 g of water was distilled off as an azeotrope with toluene produced by the reaction. After that, the reaction solution was cooled to room temperature, neutralized with 35.35 g of 15% aqueous sodium hydroxide solution, and then washed with water. After that, the toluene was distilled off while replacing it with 118.1 g of diethylene glycol monoethyl ether acetate in an evaporator, and a novolac acrylate resin solution was obtained. Next, 332.5 g of the obtained novolac type acrylate resin solution and 1.22 g of triphenylphosphine were charged into a reactor equipped with a stirrer, a thermometer, and an air inlet tube, and 60.8 g of tetrahydrophthalic anhydride was gradually added while blowing air at a rate of 10 ml / min and stirring, and the reaction was carried out at 95 to 101°C for 6 hours. A carboxyl group-containing resin with a solid acid value of 88 mgKOH / g and a solid content of 71% was obtained.

[0091] [ Reference Example 1: Working Example 2 ~ 4. Reference Example 3 and Comparative Examples 1 to 3] [Preparation of Curable Resin Composition] The components were mixed as shown in Table 1, premixed in a mixer, and then kneaded and dispersed in a three-roll mill. 、Reference example、 Curable resin compositions according to the present invention and comparative examples were also prepared. The blend amounts in the table are shown in parts by mass (solid content equivalent).

[0092] <Optimal exposure> Previous Examples 、Reference example For the curable resin composition of the comparative example and the comparative example, a circuit pattern substrate with a copper thickness of 35 μm was buff roll polished, washed with water, and dried, and then the composition was applied to the entire surface of the circuit pattern substrate by a screen printing method and dried for 60 minutes in a hot air circulation drying oven at 80° C. After drying, the composition was exposed through a step tablet (Kodak No. 2) using a projection exposure device equipped with a high-pressure mercury lamp, and development (30° C., 0.2 MPa, 1 mass % sodium carbonate aqueous solution) was performed for 60 seconds. The optimal exposure amount was determined to be when the remaining step tablet pattern had 7 steps.

[0093] <1. Resolution> The curable resin composition was diluted with methyl ethyl ketone to an appropriate viscosity and applied onto a carrier film (polyethylene terephthalate film). This was heated and dried for 30 minutes in a hot air dryer at 80°C to form a 20μm thick curable resin composition layer, and a cover film (polypropylene film) was attached onto the coating to obtain a dry film. The cover film was then peeled off, and the resulting dry film was thermally laminated onto a copper-laminated laminated substrate, exposed to a pattern at an optimal exposure dose using a projection exposure device equipped with a high-pressure mercury lamp, and developed with a 1% Na2CO3 aqueous solution at 30°C for 250 seconds under conditions of a spray pressure of 0.2MPa to form a via pattern. This substrate was then heated in a UV conveyor furnace to obtain an integrated exposure dose of 1000mJ / cm2. 2 After irradiating with ultraviolet light under the above conditions, the resin was heated at 180°C for 60 minutes to harden it. The resolution of the substrate prepared by the evaluation substrate preparation method described above was observed using an electron microscope. The via opening size was confirmed and evaluated as follows. ◎: Via pattern formation of less than φ20μm ○: Via pattern shape with diameter of 20μm or more and less than 50μm △: Via pattern shape of φ50μm or more ×: Opening shape cannot be formed

[0094] <2. Developability> The curable resin composition was diluted with methyl ethyl ketone to an appropriate viscosity and applied onto a carrier film (polyethylene terephthalate film). This was heated and dried for 30 minutes in a hot air dryer at 80°C to form a curable resin composition layer with a thickness of 20 μm, and a cover film was attached onto the resulting coating to obtain a dry film. The cover film was then peeled off, and the resulting dry film was thermally laminated onto a copper-clad laminate substrate. The resulting substrate was developed with a 1% Na2CO3 aqueous solution at 30°C under a spray pressure of 0.2 MPa for 60 seconds, and the development residue was evaluated as follows. ◎: No residue ○: Residue with a thickness of less than 1 μm △: Residue with a thickness of 1 μm or more and less than 3 μm ×: Residue with a thickness of 3 μm or more

[0095] <3. Heat resistance> The curable resin composition was diluted with methyl ethyl ketone to an appropriate viscosity and applied onto a carrier film. This was heated and dried for 30 minutes in a hot air dryer at 80°C to form a 20μm thick curable resin composition layer, and a cover film was attached onto the coating to obtain a dry film. Thereafter, the cover film was peeled off, heat laminated onto copper foil, and solidly exposed at an optimal exposure amount using a projection exposure device equipped with a high-pressure mercury lamp, and developed with a 1% Na2CO3 aqueous solution at 30°C for 250 seconds under the condition of a spray pressure of 0.2MPa. This substrate was then heated in a UV conveyor furnace to obtain an integrated exposure amount of 1000mJ / cm2. 2 After irradiating with ultraviolet light under the above conditions, the coating was cured by heating for 60 minutes at 180° C. The cured coating was peeled off from the resulting copper foil with the cured coating to obtain a cured coating film. The glass transition temperature of the resulting cured coating film was measured under the following conditions. Equipment: Dynamic viscoelasticity measuring device (Seiko Instruments Inc. DMA6100) Measurement temperature: 30~300℃ (5℃ / min) Frequency: 1Hz Glass transition temperature: The maximum value of the measured tan δ is taken as the glass transition temperature. The higher the glass transition temperature, the higher the heat resistance because the elastic change occurs at a high temperature. The evaluation criteria are as follows: ◎: 190℃ or higher ○: 180℃ or higher △: 170℃ or higher ×: Less than 170℃

[0096] <4. Breaking strength> The evaluation boards used for the heat resistance evaluation were evaluated by measuring the breaking strength in accordance with JIS K7127. The evaluation criteria were as follows: ◎: 80MPa or more ○: 40MPa or more, less than 80MPa △: Less than 40MPa

[0097] <5. Chemical resistance> The curable resin composition was diluted with methyl ethyl ketone to an appropriate viscosity, applied to a silicon wafer using a spin coater, and dried by heating for 30 minutes in a hot air dryer at 80°C to form a curable resin composition layer with a thickness of 20 μm. Solid exposure was performed at an optimal exposure amount using a projection exposure device equipped with a high-pressure mercury lamp, and development was performed for 250 seconds with a 1% Na2CO3 aqueous solution at 30°C under a spray pressure of 0.2 MPa. The substrate was then exposed to a UV conveyor furnace with an integrated exposure of 1000 mJ / cm 2 After irradiating with ultraviolet light under the conditions, the wafer was heated at 180°C for 60 minutes to cure. The obtained curable resin composition layer on the wafer was cross-cut using a cutter to form 100 square grids with sides of 1 mm. A 10% potassium hydroxide solution was heated to 40°C in a water bath, and the wafer with the cross-cut resin layer was immersed in the solution for 30 minutes. After washing with water and drying the resin layer, cellophane tape (registered trademark) was attached to the resin layer, and the chemical resistance was evaluated by peeling. The evaluation criteria are as follows. ○: No peeling △: The resin layer peels off slightly from the wafer along the cross-cut lines. ×: One or more cross-cut squares are peeled off

[0098] [Table 1]

[0099] Details of the materials listed in the table are given below. Amide-imide resin 1: Synthesized according to Synthesis Example 1 Mn=800 Amide-imide resin 2: Synthesized according to Synthesis Example 2 Mn=5800 Amide-imide resin 3: Synthesized according to Synthesis Example 3 Mn=1500 Amide-imide resin 4: Synthesized according to Synthesis Example 4 Mn=800 Photoinitiator 1: 2-methyl-1-(4-methylphenyl)-2-morpholinopropan-1-one Resin having ethylenic double bonds 1: Dipentaerythritol hexaacrylate Resin having ethylenic double bonds 2: Ethylene oxide modified trimethylolpropane triacrylate Carboxyl group-containing resin: Synthesis example 5 Thermosetting resin: Naphthol-modified epoxy resin NC-7000L (manufactured by Nippon Kayaku Co., Ltd.) Inorganic particle 1: Barium sulfate Inorganic particles 2: Silica

[0100] From the above, it is clear that the curable resin composition of the present invention not only has excellent heat resistance, but also has improved resolution, developability, breaking strength, and chemical resistance.

[0101] The present invention is not limited to the configurations and examples of the above-described embodiment, and various modifications are possible within the scope of the gist of the invention.

Claims

1. (A) an amide-imide resin; (B) a compound having an ethylenic double bond; (C) a photopolymerization initiator; (E) a carboxyl group-containing resin; Including, The (A) amide-imide resin is a reaction product between an isocyanurate-type polyisocyanate synthesized from an isocyanate having an aliphatic structure and a tricarboxylic acid anhydride, and has a number average molecular weight of 500 to 1000; The curable resin composition is characterized in that the (E) carboxyl group-containing resin does not contain an amide-imide structure and is blended in an amount of 1 part by mass or more and 40 parts by mass or less per 100 parts by mass of the solid content of the (A) amide-imide resin.

2. 2. The curable resin composition according to claim 1, wherein the tricarboxylic acid anhydride has an aliphatic structure.

3. The curable resin composition according to claim 1 or 2, further comprising (D) a thermosetting resin.

4. A dry film comprising a resin layer formed from the curable resin composition according to any one of claims 1 to 3.

5. A cured product obtained by curing the curable resin composition according to any one of claims 1 to 3 or the resin layer of the dry film according to claim 4.

6. An electronic part comprising the cured product according to claim 5.

Citation Information

Patent Citations

  • Production of imide (Amide) resin, and energy-ray-curable resin composition prepared therefrom

    JP2000344889A

  • Active ray-curing polyimide resin composition

    JP2003221429A

  • Coloring resin composition for color filter, color filter, and display

    JP2017146426A

  • Negative photocurable resin composition, dry film, cured product, and printed wiring board

    JP2018109733A

  • Alcohol-modified polyamide-imide resin and process for producing same

    WO2017221922A1